Evaluasi Mekanisme Pengelolaan Dana dengan Sistem Mudarabah Pada Asuransi Syariah (Studi Kasus di AJB Bumiputera 1912 Cabang Syariah Surakarta) - , Mujibulhaq; , Dr. Imron Rosyadi M.Ag (2017)
This study aims to determine the mechanism of fund management in AJB Bumiputera 1912 Syariah Surakarta and its conformity with the principles of Syariah in the fatwa of the National Syariah Council No: 21 / DSN-MUI / X / 2001 on General Guidelines of Syariah Insurance. This research is a type of field research, while the research used is qualitative research, data collection methods used are interviews and documentation. Descriptive evaluative being a technical writer in analyzing data. From this research can be concluded that: (1) In the management of funds, AJB Bumiputera 1912 Syariah apply 3 premium and 3 akad that is investment fund from akad muḍᾱrabah, tabarruʻ from akad tabarruʻ and ujrah from akad wakᾱlah bil ujrah (2) The mechanism of fund management in AJB Bumiputera 1912 Sharia is basically in accordance with the principles of Syariah within the DSN fatwa, but there is a difference in terms of usage of the term and also the contract which is not described in detail in the DSN fatwa. Keywords: Muḍᾱrabah, Asuransi Syariah, National Syariah Board.